Enhancing the Bystander and Abscopal Effects to Improve Radiotherapy Outcomes - Farias, Virgínea de Araújo; Tovar, Isabel; del Moral, Rosario; O'Valle, Francisco; Expósito, José; Oliver, Francisco Javier; Ruiz de Almodóvar, José Mariano (Frontiers in Oncology, 2020)
In this paper, we summarize published articles and experiences related to the attempt to predict the response of tumours and healthy tissues to radiation therapy with the aim of getting insights into their radiosensitivity and thus, to tailor the radiation treatment to the individual characteristics of each patient. The evolution of ideas and the study of successively published data have led us to imagine a new biophysical model for the interpretation of tumor response to radiation. In its development, we have shown that when human-umbilical cord mesenchymal stem cells mesenchymal cells and radiotherapy are administered simultaneously in experimental radiotherapy on xenotumors implanted in a murine model, the results of the treatment show the existence of a synergic mechanism which is able to enhance the local and systemic actions of the radiation both on the treated tumor and on its possible metastasis. We are convinced that due to the physical hallmarks that characterize the neoplastic tissues, the physical-chemical tropism of MSCs and the widespread functions of macromolecules, proteins and exosomes released from activated MSCs, the combination of radiotherapy plus MSCs intratumorally counteract the protumorigenic and pro-metastatic signals that contribute to the growth, spread, and resistance of the tumor cells. Therefore, we have concluded that the administration of MSC enhances the therapeutic effect of radiotherapy in vivo and does not produce toxic effects, indicating that they could be used as an adjuvant treatment for cancer, increasing the therapeutic effect of radiotherapy as well into the tumor as on possible the tumor-metastatic foci.